Analisis Sikap Orangtua dan Guru Terhadap Sistem Pembelajaran Daring Di Era Covid-19 Untuk Siswa Berkebutuhan Khusus Di SLBN 1 Makassar (Perspektif Pedagogis, Psikologis, dan Sosiologis) - Abdul Hadis; Djoni Rosyidi; Ponijo Ponijo (Seminar Nasional LP2M UNM, 2021)
Abstrak. The  problem  of  this  research  is  at  covid-19  era  of  online  instruction  system  for  special  need  students  is  monoton  this  bacause  students   is  not  learning  interest and  motivation.  The goal  of  this  research  is  analyzed  teacher  and  parents  to  online  instruction  system  in  Covid-19  Era  for  special  need  students  in  sociologis,  psychologis,  and  paedagogis  perspective.  Method  of  this  research  is  attitude  of  teachers  and  parents  as  single  variable,  design  of  this  research  is  descriptive,  amount  of  sample  ia  10  teacher  and  10  parents  determined  purposive  random  sampling  technique,  location  of  this  research  is  SLBN  1  Makassar,  instrument  and  data  collective  technique  is  questionnaire,  data  analysis  technique  with  percentage  descriptive  analysis.  The  result  and  conclusion  of  this  research  is  100  %  teachers  and  parents  is  positive  attitude  toward  online  instruction  system  in  paedagogis  perspective,  and  100  %  of  teachers  and  parent  is  negative  attitude  toward   online  instruction  system  in  sociologist  and  psychologist  perspective. Kata Kunci: Sikap  Orangtua,  Guru,  Daring,  Paedagogis,  Psikologis,  Sosiologis